Race, diabetes, and cognitive function: a cross-sectional analysis of intersecting disparities in the NHANES cohort - Wang, Lingling; Zhou, Qin; Yin, Yushuang; Zhang, Wenqi; Wang, Chen; Lin, Guanwen; Wu, Duozhi; Wang, Zhihua (Frontiers in Neuroscience, 2025)
BackgroundCognitive impairment poses a considerable challenge to public health systems worldwide, and its severity often varies depending on racial disparities. Diabetes, a prevalent chronic disease, is also known to adversely affect cognitive function. However, the interaction between race and diabetes in influencing cognitive function has not been well defined. This study aims to investigate the combined effects of race and diabetes on cognitive function using a demographically diverse group of elderly individuals.MethodsData were drawn from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014, involving a sample of 2,586 elderly participants aged 60 and above. Multivariate regression models were employed to assess the effects of race, diabetes status, and their interaction on cognitive test scores. Cognitive function was evaluated using the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) test, the Delayed Recall Test, the Animal Fluency Test (AFT), and the Digit Symbol Substitution Test (DSST).ResultsMexican Americans and Non-Hispanic Black people have the most frequent rates of diabetes. Non-Hispanic White people score the highest in all cognitive tests, while Mexican Americans and other Hispanics score the lowest (p < 0.001). Diabetic individuals score significantly lower than non-diabetics across all cognitive tests, with the most pronounced difference observed in DSST scores (p < 0.001). The negative association between diabetes status and DSST scores remained significant after adjusting for confounders (p < 0.001). Notably, the interaction between race and diabetes did not significantly influence cognitive function across the cognitive tests.ConclusionThis study found significant differences in diabetes prevalence and cognitive performance by race, along with a robust negative correlation between diabetes status and cognitive function. However, the interaction between race and diabetes does not significantly affect cognitive function.